PERTANGGUNG JAWABAN PERBUATAN ADMINISTRASI NEGARA OLEH INSTITUSI PUBLIK (STUDI GUGATAN PERBUATAN MELAWAN HUKUM PT BUMI ASIH JAYA TERHADAP OTORITAS JASA KEUANGAN DALAM PUTUSAN NOMOR 643/Pdt.G/2017/PN.Jkt.Pst.) - Andari Yurikosari (Hukum Pidana dan Pembangunan Hukum, 2018)
Through the Commercial Court, the Financial Services Authority (OJK) managed to bankrupt PT Asuransi Bumi Asih Jaya and OJK won the case until the Judicial Review (PK) stage. At the time of the bankruptcy process, PT Asuransi Bumi Asih Jaya, again sued OJK for unlawful conduct and was registered at the Central Jakarta Commercial Court with number 643 / Pdt.G / 2017 / PN.Jkt.Pst. This is because PT Asuransi Bumi Asih Jaya as the plaintiff did not accept the arbitrary actions carried out by OJK. PT Asuransi Bumi Asih Jaya sued for compensation of Rp.4.4 trillion, with details of material losses worth Rp1.4 trillion. Losses are calculated since the OJK revoked its business license in October 2013. To be able to carry out its duties and functions, the state administration carries out various acts or activities of state administration which are often referred to as state administrative actions or acts of state administration. State administration actions became important later when dealing with cases such as in the case of PT Asuransi Bumi Asih Jaya's lawsuit, in which the company sued OJK as a state institution which as a state administration official had committed a violation in the conduct of state administration. The main problem in this study is how the actions of the Asuransi Bumi Asih Jaya company sued the Financial Services Authority as a public body with a lawsuit against the law and how to analyze the position of the Financial Services Authority in legally responsible state administrative actions that have been carried out against PT Asuransi Bumi Asih Jaya. The study was conducted using normative research methods, with qualitative descriptive analysis. The results of the study illustrate that if there is a violation in the conduct of state administration, the state legal entity that is a public institution can be sued through the District Court in the case of a civil case if it has committed a violation of state administrative law.Keywords: acts of state administrative law, public legal entities, acts against the law